2022
DOI: 10.1055/s-0040-1719908
|View full text |Cite
|
Sign up to set email alerts
|

Epoxydibenzo[b,f][1,5]diazocines: From a Hidden Structural Motif to an Efficient Solvent-Free Synthetic Protocol

Abstract: Epoxydiazocines belong to the rare class of small V-shaped molecules, closely related to Tröger’s base. Due to their intriguing, unique structure, they could serve as molecular building blocks for supramolecular chemistry. An extensive review on their synthesis is contained in this article. Moreover, our recent findings devoted to efficient and easily scalable synthesis of fluorinated epoxy[1,5][b,f]diazocines through solvent-free base-catalyzed condensation of ortho-aminophenones is provided. The unique V-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Synthetic protocols for the preparation of epoxydibenzo [1,5] diazocine are rarely reported. 77 In 2011, Wang et al 78 showed the analogue can be obtained from the reaction of 2-amino-6bromo-4-(trifluoromethyl)benzaldehyde, phenyl ketone, 57a and sodium hydroxide in refluxing ethanol. Product 58 was synthesised in 40% yield with accompanying formation of substituted quinoline, 59 in 15% yield.…”
Section: Synthesis and Functionalisation Of Epoxydibenzo[15]diazocinesmentioning
confidence: 99%
“…Synthetic protocols for the preparation of epoxydibenzo [1,5] diazocine are rarely reported. 77 In 2011, Wang et al 78 showed the analogue can be obtained from the reaction of 2-amino-6bromo-4-(trifluoromethyl)benzaldehyde, phenyl ketone, 57a and sodium hydroxide in refluxing ethanol. Product 58 was synthesised in 40% yield with accompanying formation of substituted quinoline, 59 in 15% yield.…”
Section: Synthesis and Functionalisation Of Epoxydibenzo[15]diazocinesmentioning
confidence: 99%